Germany - Ciesielska-Klikowska, Joanna (The Role of Regions in EU-China Relations, 2021)
The aim of the chapter is to analyse how Germany cooperates with China at the substate level. The authors try to highlight the background of the bilateral relations and answer the questions about the grounds for German multidimensional cooperation with China and its transformation in recent years.The chapter consists of three main parts. The first one concentrates on a description of the political, economic and social relations at the interstate level. Firstly, it presents the genesis of political relations between the Federal Republic of Germany and the People’s Republic of China, as well as how they have evolved until today. Secondly, the data on the economic exchange of recent years and the importance of bilateral cooperation between states in economic dimension is presented. Thirdly, in the section devoted to people-to-people contacts, the authors focus on the importance of the Chinese diaspora in Germany, the number of Chinese students and the role played by Confucius Institutes.The second part of the chapter discusses the theoretical background of international cooperation of German Bundesländer and their position as policy actors on the global scene.The third section presents the outcomes of a survey conducted among German regions and the results of interviews with officials in selected regional authorities and in the German MFA. This final part describes moreover German paradiplomatic relations with Chinese counterparts. This section is supplemented by a case study of the land of Berlin and its cooperation with China.